Perancangan UI/UX Aplikasi Mobile “Tour Kei” Sebagai Pemandu Wisata Maluku Tenggara Menggunakan Metode Design Thinking - Renwarin, Pio Mario; Jatmiko, Andriyan Rizki (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Kei Islands is an archipelago that holds a lot of natural beauty, many tourists enter every year for a vacation. Guide is a very important field in tourism, where this guide is tasked with providing information to tourists. However, the existing guide services are lacking so that incoming tourists sometimes do not get a guide and are confused about where to start the journey and rarely get information about the destinations visited, therefore in this study try to give ideas to the Tourism Office in the form of designing UI / UX applications “Tour Kei” which become digital guides in increasing the tourism potential of the Kei islands. The design results will be calculated using the SUS calculation method, with the results of the score being at 81 in the “Acceptable” category with a grade scale of “A” and a rating at the “Excellent” level. With these results the design idea is well received and meets the level of use.